The role of common factors in residential cognitive and interpersonal therapy for social phobia: a process-outcome study. - Hoffart, A; Borge, F; Sexton, H; Clark, D (2009)
This study examined the role of common factors in residential cognitive therapy (RCT) and residential interpersonal therapy (RIPT) for social phobia. Eighty social phobic patients were randomized to 10 weeks of RCT or RIPT. Patients and their individual therapists completed process and suboutcome measures weekly. The ratings were examined using linear mixed models. Most patient-rated process variables showed U-shaped (quadratic) patterns over the course of treatment. Therapist-rated alliance increased linearly. Therapist-rated first-week alliance and empathy predicted improvement in social role security over the course of therapy. The weekly fluctuations in common process predicted subsequent fluctuations in suboutcomes in seven of 10 possible cases, whereas suboutcomes predicted process in four cases. The results support the causal role of common factors.